PENGARUH PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN, BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN TINGKAT KEMISKINAN TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DI PROVINSI JAWA TENGAH TAHUN 2021-2024 (Studi Kasus pada Kabupaten/Kota di Provinsi Jawa Tengah Periode 2021-2024) - Bintang Dwi Kristiastanto; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2026)
This study examines the effect of Rural and Urban Land and Building Tax (PBB-P2), Land and Building Acquisition Duty (BPHTB), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Poverty Rate on the Human Development Index (HDI). The study was conducted across all regencies and municipalities in Central Java Province for the 2021–2024 period, motivated by persistent HDI disparities across districts and the limited studies simultaneously incorporating local tax, fiscal transfer, and poverty variables. This study employs a quantitative approach using multiple linear regression on 140 panel data observations obtained through saturated sampling of 35 regencies and municipalities. Data were sourced from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance of the Republic of Indonesia. Fiscal variables were transformed into natural logarithm form, and hypotheses were tested through t-test, F-test, and Adjusted R², preceded by classical assumption tests. The F-test confirms that all variables simultaneously and significantly affect HDI, with an F value of 60.417 and a significance level of 0.000, while the Adjusted R² of 0.681 indicates that the independent variables explain 68.1% of HDI variation. Partially, BPHTB has a positive and significant effect on HDI, as does DAU. In contrast, DAK has a negative and significant effect on HDI, suggesting that increases in DAK have not directly improved human development quality in the short run. Meanwhile, PBB-P2 and Poverty Rate show no significant effect on HDI.